1995
DOI: 10.1038/374647a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of microglial cells by β-amyloid protein and interferon-γ

Abstract: Alzheimer's disease is the most common cause of progressive intellectual failure. The lesions that develop, called senile plaques, are extracellular deposits principally composed of insoluble aggregates of beta-amyloid protein (A beta), infiltrated by reactive microglia and astrocytes. Although A beta, and a portion of it, the fragment 25-35 (A beta (25-35)), have been shown to exert a direct toxic effect on neurons, the role of microglia in such neuronal injury remains unclear. Here we report a synergistic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
778
3
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,258 publications
(834 citation statements)
references
References 21 publications
39
778
3
7
Order By: Relevance
“…4 These proliferated microglia possibly accelerate neuronal damage by releasing toxic substances. [6][7][8] We previously reported that microglial proliferation and activation were observed in the damaged spinal cord, and that the time course of the progress of hind-limb function loss was quite similar to that of the microglia proliferation in spinal cord after a compression injury. The proliferated microglia were positively stained by anti-TNF-a and anti-iNOS antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 These proliferated microglia possibly accelerate neuronal damage by releasing toxic substances. [6][7][8] We previously reported that microglial proliferation and activation were observed in the damaged spinal cord, and that the time course of the progress of hind-limb function loss was quite similar to that of the microglia proliferation in spinal cord after a compression injury. The proliferated microglia were positively stained by anti-TNF-a and anti-iNOS antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…These pathologically activated microglia accelerate neuronal damage by releasing nitric oxide, superoxide and inflammatory cytokines such as TNF-a. [6][7][8] Previously, we developed a model for mild spinal cord compression injuries using rats. 9 In this model, microglia proliferated and were activated after spinal cord compression.…”
Section: Introductionmentioning
confidence: 99%
“…These pro-inflammatory cytokines stimulate inflammatory cells to release damaging reactive oxygen and nitrogen species, raise glutamate levels to excitotoxic levels, impair the ability of glia cells to buffer extracellular potassium, compromise the blood-brain barrier, and attract more inflammatory cells into the brain (Tanaka et al, 1994, Meda et al, 1995, Soares et al, 1995, Hu et al, 1997, Keeling et al, 2000. Once initiated, the inflammatory cascade becomes a toxic positivefeedback loop, further exacerbating brain pathology.…”
mentioning
confidence: 99%
“…Alternative therapeutic strategies against amyloid toxicity could increase proteostatic capacity or target reactive oxygen species (ROS). It has been described that deposition of misfolded proteins increases the amount of ROS [37], by causing inflammation in neuroglia, which, in turn, catalyzes ROS formation [38,39]. Aβ, αS, and PrP also complex metal ions, such as FeII and CuI, that strongly catalyze ROS formation [40,41].…”
Section: Toxicity and Amyloid Formationmentioning
confidence: 99%